Adaptación psicométrica de la Batería de Evaluación de los Procesos Lectores Revisada (PROLEC-R) - Cayhualla, Nidia (2013)
The present study aims at adapting psychometric Assessment Battery Revised Readers Processes (PROLEC-R). The Battery applied linguistics and pictographically adapted to a group of 504 students from 14 educational institutions in metropolitan Lima, 7 from private institutions and 7 public institutions of both sexes. Such analysis indicated that scores of PROLEC-R adapted to be reliable, calculated by the method of internal consistency (Cronbach’s alpha) for sub test and total. Also validates evidence of the content (expert opinion), criterion (concurrent validity) and construct (confirmatory factor analysis).